Upaya Guru dalam Mewujudkan Pembelajaran SKI yang Menyenangkan di MIN 1 Medan - Nasution, Abdul Gani Jamora; Aina, Tasha; Prayudha, Reyhan (Lembaga Yasin AlSys, 2023)
The purpose of learning SKi in MI is to build students' awareness about the importance of learning the basic teachings, values and Islamic norms that have been built by the Prophet Muhammad in order to develop Islamic culture and civilization. The purpose of this study was to find out the efforts of SKI teachers in realizing fun SKI learning at MIN 1 Medan, based on the results of our research one of the teachers at MIN Medan mentioned several fun learning steps 1. The teacher greets with greetings and provides motivation to students; 2. Instilling positive feelings in students and the meaningfulness of the subject matter with life, this can be done by telling a short story and giving an example contextually; 3. Show interactive videos related to the material and ask students to re-explain the meaning of the show from the student's point of view; 4. Invite students to play while learning. For example asking students to make their own questions and then exchanging them with other students and then students correcting questions that have been made and done by fellow students; 5. Students are grouped into groups of three to play the game